The power of no (Assemble You, 2022)
Welcome to Audio Learning from Assemble You. Saying yes comes naturally - as human beings, it makes us feel good to help others. But what doesn't feel good is the stress that comes with built-up project deadlines you're struggling to meet because you took too much on. In this audio lesson we offer practical, actionable advice on how to say no more often and take control of your day. Learning Objectives Learn why saying yes is not always helpful to those asking for help Learn techniques to help you make the right call on what to say yes to Learn the right communication techniques to make saying no easy.